Flight demonstration of a CubeSat Sporadic-E detector - Bruce A. Fritz; Kenneth F. Dymond; Ellen J. Wagner; Andrew C. Nicholas; Scott A. Budzien; Andrew W. Stephan (Advances in Space Research, 2026)

Illuminating plant metabolism with genetically encoded biosensors - Stephan Wagner; Andreas J. Meyer (Journal of Plant Physiology, 2025)

Oxidative purification of microplastics in riverine suspended matter samples — Solving the challenge of plant debris removal for microplastic analysis - Orasai Faikhaw; Stephan Wagner; Robby Rynek; Guyu Peng; Dušan Materić; Thorsten Reemtsma (Science of The Total Environment, 2025)

Teaching Research Data Management with DataLad: A Multi-year, Multi-domain Effort - Michał Szczepanik; Adina S. Wagner; Stephan Heunis; Laura K. Waite; Simon B. Eickhoff; Michael Hanke (Neuroinformatics, 2024)
Research data management has become an indispensable skill in modern neuroscience. Researchers can benefit from following good practices as well as from having proficiency in using particular software solutions. But as these domain-agnostic skills are commonly not included in domain-specific graduate education, community efforts increasingly provide early career scientists with opportunities for organised training and materials for self-study. Investing effort in user documentation and interacting with the user base can, in turn, help developers improve quality of their software. In this work, we detail and evaluate our multi-modal teaching approach to research data management in the DataLad ecosystem, both in general and with concrete software use. Spanning an online and printed handbook, a modular course suitable for in-person and virtual teaching, and a flexible collection of research data management tips in a knowledge base, our free and open source collection of training material has made research data management and software training available to various different stakeholders over the past five years.

The chemical composition and sources of road dust, and of tire and road wear particles–A review - Stephan Wagner; Christopher Werner Funk; Kathrin Müller; David Joshua Raithel (Science of The Total Environment, 2024)

Accelerated aging of tire and road wear particles by elevated temperature, artificial sunlight and mechanical stress — A laboratory study on particle properties, extractables and leachables - Steffen Weyrauch; Bettina Seiwert; Milena Voll; Stephan Wagner; Thorsten Reemtsma (Science of The Total Environment, 2023)

Ex vivo models for intestinal translocation studies of cellulose nanocrystals - Michelle Müller; Roland Drexel; Marie Burkhart; Stephan Dähnhardt-Pfeiffer; Lena Wien; Christine Herrmann; Thorsten Knoll; Christoph Metzger; Heiko Briesen; Sylvia Wagner; Florian Meier; Yvonne Kohl (In vitro models, 2023)
Purpose Cellulose nanocrystals (CNC) play a promising role in the development of new advanced materials. The growing demand of CNC-containing products in the food industry will lead to an increased human exposure through oral uptake. To date, there is a dearth of studies reporting on the risks which CNC pose to human health following ingestion. In vitro models, which lack physiological accuracy, are often used to justify animal experiments in the field of nanosafety assessment. Nevertheless, ex vivo models of the intestine pose promising alternatives to in vivo experiments. Methods Two ex vivo models, a microfluidic chip based on porcine intestinal mucus and the Ussing chamber apparatus with tissue from abattoirs, which aim to complement in vitro models, are characterized by investigating the transport and toxicity of CNC through them in comparison to an in vitro triple co-culture model. Silver nanoparticles were included in this study as well-known and characterized nanomaterials for comparative purposes. Results Study results show that CNC cross the intestinal mucus layer but do not pass the intestinal tissue barrier ex vivo and in vitro; furthermore, no toxic effects were observed under exposure conditions tested. Conclusion These ex vivo models present complementary methods to the existing standardized in vitro and in silico methods to support data generation under physiologically relevant conditions without the use of animals. This multi-model approach offers an enhanced understanding of the complex interaction between new materials and human tissue and aligns with the flexible approach of IATA (Integrated Approaches to Testing and Assessment) and NAMs (New Approach Methods) for chemical and drug safety assessment.

Light stable Cr isotope compositions of mid-ocean ridge basalts: Implications for mantle source composition - Luise J. Wagner; Ilka C. Kleinhanns; Maria I. Varas-Reus; Carolina Rosca; Stephan König; Wolfgang Bach; Ronny Schoenberg (Geochimica et Cosmochimica Acta, 2023)

Mercury biomonitoring in German adults using volumetric absorptive microsampling - Anastasia Koutsimpani-Wagner; Caroline Quartucci; James P. K. Rooney; Stephan Bose-O’Reilly; Stefan Rakete (Environmental Monitoring and Assessment, 2022)
Mercury (Hg) is a global pollutant and a danger to human health. Human biomonitoring of Hg using a dried blood matrix instead of venous blood sampling for exposure assessment is of growing interest. This study aims to develop, validate, and evaluate the application of volumetric absorptive microsampling (VAMS) for Hg biomonitoring in humans. Sampling, drying, and storage conditions were evaluated during method development. Storage in pre-cleaned glass vials after drying for 2 h in a desiccator ensured analyte stability for at least 4 weeks. Sixty-eight paired capillary VAMS and venous blood samples from volunteers in Munich, Germany, were used for method validation. Hg levels in VAMS and venous blood samples were determined by direct mercury analysis. The limits of detection and quantitation for VAMS were 0.18 and 0.61 µg/l, respectively. However, sensitivity could be improved by using two microsamples for analysis instead of one. Hg levels in VAMS samples correlated very well with Hg levels in venous blood samples (R 2 = 0.958). Furthermore, VAMS showed a high accuracy (median recovery: 117%) and precision (median relative standard deviation: 8.7%), especially for Hg concentrations above 1.0 µg/l. In fact, accuracy and precision of VAMS improved with increasing Hg concentrations. In conclusion, VAMS in combination with direct mercury analysis is an accurate and viable alternative for human biomonitoring of Hg. Graphical abstract

Spatio-temporal occurrence patterns of epibiota along the leaves of the seagrass Cymodocea nodosa in the Northern Adriatic Sea - Sandra Bračun; Maximilian Wagner; Stephan Koblmüller (Marine Biology Research, 2021)

sPlotOpen – An environmentally balanced, open‐access, global dataset of vegetation plots - Francesco Maria Sabatini; Jonathan Lenoir; Tarek Hattab; Elise Aimee Arnst; Milan Chytrý; Jürgen Dengler; Patrice De Ruffray; Stephan M. Hennekens; Ute Jandt; Florian Jansen; Borja Jiménez‐Alfaro; Jens Kattge; et al. (Global Ecology and Biogeography, 2021)
Motivation Assessing biodiversity status and trends in plant communities is critical for understanding, quantifying and predicting the effects of global change on ecosystems. Vegetation plots record the occurrence or abundance of all plant species co‐occurring within delimited local areas. This allows species absences to be inferred, information seldom provided by existing global plant datasets. Although many vegetation plots have been recorded, most are not available to the global research community. A recent initiative, called ‘sPlot’, compiled the first global vegetation plot database, and continues to grow and curate it. The sPlot database, however, is extremely unbalanced spatially and environmentally, and is not open‐access. Here, we address both these issues by (a) resampling the vegetation plots using several environmental variables as sampling strata and (b) securing permission from data holders of 105 local‐to‐regional datasets to openly release data. We thus present sPlotOpen, the largest open‐access dataset of vegetation plots ever released. sPlotOpen can be used to explore global diversity at the plant community level, as ground truth data in remote sensing applications, or as a baseline for biodiversity monitoring. Main types of variable contained Vegetation plots ( n = 95,104) recording cover or abundance of naturally co‐occurring vascular plant species within delimited areas. sPlotOpen contains three partially overlapping resampled datasets ( c . 50,000 plots each), to be used as replicates in global analyses. Besides geographical location, date, plot size, biome, elevation, slope, aspect, vegetation type, naturalness, coverage of various vegetation layers, and source dataset, plot‐level data also include community‐weighted means and variances of 18 plant functional traits from the TRY Plant Trait Database. Spatial location and grain Global, 0.01–40,000 m². Time period and grain 1888–2015, recording dates. Major taxa and level of measurement 42,677 vascular plant taxa, plot‐level records. Software format Three main matrices (.csv), relationally linked.

Haploinsufficiency of the HIRA gene located in the 22q11 deletion syndrome region is associated with abnormal neurodevelopment and impaired dendritic outgrowth - Médéric Jeanne; Marie-Laure Vuillaume; Dévina C. Ung; Valerie E. Vancollie; Christel Wagner; Stephan C. Collins; Sandrine Vonwill; Damien Haye; Nora Chelloug; Rolph Pfundt; Joost Kummeling; Marie-Pierre Moizard; et al. (Human Genetics, 2021)

Unravelling the taxonomy of an interstitial fish radiation: Three new species of Gouania (Teleostei: Gobiesocidae) from the Mediterranean Sea and redescriptions of G. willdenowi and G. pigra - Maximilian Wagner; Marcelo Kovačić; Stephan Koblmüller (Journal of Fish Biology, 2021)
The clingfish (Gobiesocidae) genus Gouania Nardo, 1833 is endemic to the Mediterranean Sea and inhabits, unlike any other vertebrate species in Europe, the harsh intertidal environment of gravel beaches. Following up on a previous phylogenetic study, we revise the diversity and taxonomy of this genus by analysing a comprehensive set of morphological (meristics, morphometrics, microcomputed tomography imaging), geographical and genetic (DNA‐barcoding) data. We provide descriptions of three new species, G. adriatica sp. nov. , G. orientalis sp. nov. and G. hofrichteri sp. nov. , as well as redescriptions of G. willdenowi (Risso, 1810) and G. pigra (Nardo, 1827) and assign neotypes for the latter two species. In addition to elucidating the complex taxonomic situation of Gouania , we discuss the potential of this enigmatic clingfish genus for further ecological, evolutionary and biodiversity studies that might unravel even more diversity in this unique Mediterranean fish radiation.

Phylogeographic structure and population connectivity of a small benthic fish ( Tripterygion tripteronotum ) in the Adriatic Sea - Kristina M. Sefc; Maximilian Wagner; Lukas Zangl; Sara Weiß; Bernd Steinwender; Paul Arminger; Theresa Weinmaier; Nejra Balkic; Tobias Kohler; Silvio Inthal; Marcelo Kovačić; Stamatis Zogaris; et al. (Journal of Biogeography, 2020)
Aim Population connectivity of benthic marine organisms depends strongly on planktonic larval dispersal and is controlled by geographic distance and oceanographic structure. We examine isolation by distance versus resistance to barriers (ocean current boundaries) against a background of post‐glacial habitat expansion in a small benthic fish of the Adriatic Sea. Location Adriatic Sea, Eastern Mediterranean. Taxon Tripterygion tripteronotum . Methods We performed population genetic analyses using mitochondrial control region sequences of 550 individuals from 25 locations sampled along the Eastern Adriatic coast. Investigations of population structure included differentiation tests, cluster analyses and distance‐based redundancy analysis. We then ran Lagrangian simulations of passive larval drift to examine correlations among population structure, geographic distance and the Adriatic gyre system. To test for signatures of a post‐glacial range expansion, we modelled the demographic history of the populations and examined the geographic distribution of genetic diversity. Results Genetic population structure corresponded to the Adriatic gyres without additional effect of geographic distance. Inference of northward‐biased gene flow between the northern and the Istrian gyre was consistent with simulated trajectories of passive drift, whereas the phylogeographic break coinciding with the boundary between the Central and the Northern Adriatic gyre was stronger than predicted by drift simulations. Genetic connectivity of populations within gyres was high. Genetic signatures of population expansion were consistent with a rapid post‐glacial recolonization of the northern Adriatic. Main conclusions The combination of dense sampling and passive drift simulation allowed us to distinguish among effects of geographic distance, oceanographic features and palaeoenvironmental changes on current population structure. Comparisons between realized and potential connectivity illustrate the value of integrating different data sources to understand population structure and inform conservation planning.

Alterations of the renin angiotensin system in human end-stage heart failure before and after mechanical cardiac unloading by LVAD support - Rebecca Messmann; Alexander Dietl; Stefan Wagner; Oliver Domenig; Carsten Jungbauer; Andreas Luchner; Lars S. Maier; Simon Schopka; Stephan Hirt; Christof Schmid; Christoph Birner (Molecular and Cellular Biochemistry, 2020)
Heart transplantation is often an unrealizable therapeutic option for end-stage heart failure, which is why mechanical left ventricular assist devices (LVADs) become an increasingly important therapeutic alternative. Currently, there is a lack of information about molecular mechanisms which are influenced by LVADs, particularly regarding the pathophysiologically critical renin angiotensin system (RAS). We, therefore, determined regulation patterns of key components of the RAS and the β-arrestin signaling pathways in left ventricular (LV) tissue specimens from 8 patients with end-stage ischemic cardiomyopathy (ICM) and 12 patients with terminal dilated cardiomyopathy (DCM) before and after LVAD implantation and compared them with non-failing (NF) left ventricular tissue samples: AT1R, AT2R, ACE, ACE2, MasR, and ADAM17 were analyzed by polymerase chain reaction. ERK, phosphorylated ERK, p38, phosphorylated p38, JNK, phosphorylated JNK, GRK2, β-arrestin 2, PI3K, Akt, and phosphorylated Akt were determined by Western blot analysis. Angiotensin I and Angiotensin II were quantified by mass spectrometry. Patients were predominantly middle-aged (53 ± 10 years) men with severely impaired LV function (LVEF 19 ± 8%), when receiving LVAD therapy for a mean duration of 331 ± 317 days. Baseline characteristics did not differ significantly between ICM and DCM patients. By comparing failing with non-failing left ventricles, i.e., before LVAD implantation, a downregulation of AT1R, AT2R, and MasR and an upregulation of ACE, ACE2, GRK, β-arrestin, ERK, PI3K, and Akt were seen. Following LVAD support, then angiotensin I, ACE2, GRK, and β-arrestin were downregulated and AT2R, JNK, and p38 were upregulated. ACE, angiotensin II, AT1R, ADAM17, MasR, ERK, PI3K, and Akt remained unchanged. Some regulation patterns were influenced by the underlying etiology of heart failure, the severity of LV dysfunction at baseline, and the duration of LVAD therapy. Key components of the RAS and β-arrestin signaling pathways were divergently altered in failing left ventricles both before and after LVAD implantation, whereas a remarkable fraction remained unchanged. This indicates a rather incomplete molecular reverse remodeling, whose functional relevance has to be further evaluated.

“A reference genome assembly and adaptive trait analysis of Castanea mollissima ‘Vanuxem,’ a source of resistance to chestnut blight in restoration breeding” - Margaret Staton; Charles Addo-Quaye; Nathaniel Cannon; Jiali Yu; Tetyana Zhebentyayeva; Matthew Huff; Nurul Islam-Faridi; Shenghua Fan; Laura L. Georgi; C. Dana Nelson; Emily Bellis; Sara Fitzsimmons; et al. (Tree Genetics & Genomes, 2020)

The impact of endurance training and table soccer on brain metabolites in schizophrenia - Boris-Stephan Rauchmann; Farhad Ghaseminejad; Daniel Keeser; Katriona Keller-Varady; Thomas Schneider-Axmann; Shun Takahashi; Temmuz Karali; Gunther Helms; Peter Dechent; Isabel Maurus; Alkomiet Hasan; Thomas Wobrock; et al. (Brain Imaging and Behavior, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Tissue engineering and regenerative medicine in musculoskeletal oncology - Boris Michael Holzapfel; Ferdinand Wagner; Laure Christine Martine; Stephan Reppenhagen; Maximilian Rudert; Michael Schuetz; Jim Denham; Jan-Thorsten Schantz; Dietmar Werner Hutmacher (Cancer and Metastasis Reviews, 2016)

Cortical thinning in former professional soccer players - Inga K. Koerte; Michael Mayinger; Marc Muehlmann; David Kaufmann; Alexander P. Lin; Denise Steffinger; Barbara Fisch; Boris-Stephan Rauchmann; Stefanie Immler; Susanne Karch; Florian R. Heinen; Birgit Ertl-Wagner; et al. (Brain Imaging and Behavior, 2016)

Development of a mobbing short scale in the Gutenberg Health Study - Susan Garthus-Niegel; Matthias Nübling; Stephan Letzel; Janice Hegewald; Mandy Wagner; Philipp S. Wild; Maria Blettner; Isabella Zwiener; Ute Latza; Sylvia Jankowiak; Falk Liebers; Andreas Seidler (International Archives of Occupational and Environmental Health, 2016)

A phenomenological approach shows a high coherence of warming patterns in dimictic aquatic systems across latitude - Annekatrin Wagner; Stephan Hülsmann; Lothar Paul; Rüdiger J. Paul; Thomas Petzoldt; René Sachse; Thomas Schiller; Bettina Zeis; Jürgen Benndorf; Thomas U. Berendonk (Marine Biology, 2012)

Iron oxide mineralogy and stable iron isotope composition in a Gleysol with petrogleyic properties - Tim Mansfeldt; Stephan Schuth; Werner Häusler; Friedrich E. Wagner; Stephan Kaufhold; Mark Overesch (Journal of Soils and Sediments, 2012)

TRPM3 channels provide a regulated influx pathway for zinc in pancreatic beta cells - Thomas F. J. Wagner; Anna Drews; Sabine Loch; Florian Mohr; Stephan E. Philipp; Sachar Lambert; Johannes Oberwinkler (Pflügers Archiv - European Journal of Physiology, 2010)

Testing In Situ Sulfate Reduction by H2 injection in a Bench-Scale Column Experiment - Felix Bilek; Stephan Wagner (Water, Air, & Soil Pollution, 2009)

Reverse dissimilatory sulfite reductase as phylogenetic marker for a subgroup of sulfur‐oxidizing prokaryotes - Alexander Loy; Stephan Duller; Christian Baranyi; Marc Mußmann; Jörg Ott; Itai Sharon; Oded Béjà; Denis Le Paslier; Christiane Dahl; Michael Wagner (Environmental Microbiology, 2009)
Summary Sulfur‐oxidizing prokaryotes (SOP) catalyse a central step in the global S‐cycle and are of major functional importance for a variety of natural and engineered systems, but our knowledge on their actual diversity and environmental distribution patterns is still rather limited. In this study we developed a specific PCR assay for the detection of dsrAB that encode the reversely operating sirohaem dissimilatory sulfite reductase (rDSR) and are present in many but not all published genomes of SOP. The PCR assay was used to screen 42 strains of SOP (most without published genome sequence) representing the recognized diversity of this guild. For 13 of these strains dsrAB was detected and the respective PCR product was sequenced. Interestingly, most dsrAB ‐encoding SOP are capable of forming sulfur storage compounds. Phylogenetic analysis demonstrated largely congruent rDSR and 16S rRNA consensus tree topologies, indicating that lateral transfer events did not play an important role in the evolutionary history of known rDSR. Thus, this enzyme represents a suitable phylogenetic marker for diversity analyses of sulfur storage compound‐exploiting SOP in the environment. The potential of this new functional gene approach was demonstrated by comparative sequence analyses of all dsrAB present in published metagenomes and by applying it for a SOP census in selected marine worms and an alkaline lake sediment.

Mind the bend: cerebral activations associated with mental imagery of walking along a curved path - Judith Wagner; Thomas Stephan; Roger Kalla; Hartmut Brückmann; Michael Strupp; Thomas Brandt; Klaus Jahn (Experimental Brain Research, 2008)

Environmental genomics reveals a functional chlorite dismutase in the nitrite‐oxidizing bacterium ‘ Candidatus Nitrospira defluvii’ - Frank Maixner; Michael Wagner; Sebastian Lücker; Eric Pelletier; Stephan Schmitz‐Esser; Karin Hace; Eva Spieck; Robert Konrat; Denis Le Paslier; Holger Daims (Environmental Microbiology, 2008)
Summary Nitrite‐oxidizing bacteria of the genus Nitrospira are ubiquitous in natural ecosystems and also in wastewater treatment plants. Nitrospira are members of a distinct phylum, not closely related to other nitrifiers, and no genomic sequences from this genus have been available so far. Here we applied an environmental genomics approach to sequence and assemble a 137 kbp‐long genome fragment of ‘ Candidatus Nitrospira defluvii’, which had been enriched from activated sludge and belongs to Nitrospira sublineage I without isolated representatives. The annotation of this contig, which carried the 16S rRNA gene of N. defluvii , offered first insight into the genome of Nitrospira . Surprisingly, we found a gene similar to genes encoding chlorite dismutase (CLD), an enzyme degrading chlorite (ClO 2 ‐ ) to Cl ‐ and O 2 . To date, CLDs with high catalytic activity have been found only in perchlorate‐ and chlorate‐reducing bacteria but not in nitrifiers. Heterologous expression in E. coli followed by enzymatic tests confirmed that this gene of Nitrospira encodes a highly active CLD, which is also expressed in situ by Nitrospira , indicating that this nitrite oxidizer might be involved in the bioremediation of perchlorate and chlorite. Phylogenetic analyses showed that CLD and related proteins are widely distributed among the Bacteria and Archaea , and indicated that this enzyme family appeared relatively early in evolution, has been subject to functional diversification and might play yet unknown roles in microbial metabolism.

Multiple defence strategies of Daphnia galeata against predation in a weakly stratified reservoir - Stephan Hülsmann; Annekatrin Wagner (Hydrobiologia, 2007)

The feeding behaviour of large perch Perca fluviatilis (L.) in relation to food availability: a comparative study - Hendrik Dörner; Søren Berg; Lene Jacobsen; Stephan Hülsmann; Mads Brojerg; Annekatrin Wagner (Hydrobiologia, 2003)

16S‐23S rDNA intergenic spacer and 23S rDNA of anaerobic ammonium‐oxidizing bacteria: implications for phylogeny and in situ detection - Markus Schmid; Stephan Schmitz‐Esser; Mike Jetten; Michael Wagner (Environmental Microbiology, 2001)
Recently, anaerobic ammonium‐oxidizing bacteria (AAOB) were identified by comparative 16S rDNA sequence analysis as a novel, deep‐branching lineage within the Planctomycetales . This lineage consists currently of only two, not yet culturable bacteria which have been provisionally described as Candidatus ‘Brocadia anammoxidans’ and Candidatus ‘Kuenenia stuttgartiensis’. In this study, a large fragment of the rDNA operon, including the 16S rDNA, the intergenic spacer region (ISR) and approximately 2 000 bases of the 23S rDNA, was polymerase chain reaction (PCR) amplified, cloned and sequenced from both AAOB. The retrieved 16S rDNA sequences of both species contain an insertion at helix 9 with a previously overlooked pronounced secondary structure (new subhelices 9a and 9b). This insertion, which is absent in all other known prokaryotes, is detectable by fluorescence in situ hybridization (FISH) and thus present in the mature 16S rRNA. In contrast with the genera Pirellula , Planctomyces and Gemmata that possess unlinked 16S and 23S rRNA genes, both AAOB have the respective genes linked together by an ISR of approximately 450 bp in length. Phylogenetic analysis of the obtained 23S rRNA‐genes confirmed the deep branching of the AAOB within the Planctomycetales and allowed the design of additional specific FISH probes. Remarkably, the ISR of the AAOB also could be successfully detected by FISH via simultaneous application of four monolabelled oligonucleotide probes. Quantitative FISH experiments with cells of Candidatus ‘Brocadia anammoxidans’ that were inhibited by exposure to oxygen for different time periods demonstrated that the concentration of transcribed ISR reflected the activity of the cells more accurately than the 16S or 23S rRNA concentration. Thus the developed ISR probes might become useful tools for in situ monitoring of the activity of AAOB in their natural environment.